Application of thiophene derivative in inorganic perovskite photovoltaic device

By using thiophene derivative NMTC as an additive in inorganic perovskite photovoltaic devices, the crystallization process is regulated, the perovskite absorbing layer is optimized, and the inorganic perovskite photovoltaic devices with an inverted structure are solved. Inorganic perovskite photovoltaic devices are solved in the weak light The poor performance problem under conditions achieves efficient photovoltaic performance and good thermal stability.

CN119233741APending Publication Date: 2024-12-31SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411159239.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Inorganic perovskite photovoltaic devices have low photoelectric conversion efficiency under low light conditions and high defect state density, making it difficult to perform excellent photovoltaic performance under standard sunlight and low light conditions.

Method used

Using the thiophene derivative N-methylbenzo[b]thiophene-3-acetamide (NMTC) as an additive, the crystallization process of inorganic perovskite films is regulated, the structure of the perovskite absorbing layer is optimized, and the inorganic structure of inverted structures is constructed. Perovskite photovoltaic devices.

Benefits of technology

A photoelectric conversion efficiency of 16.08% was achieved under standard sunlight and a photoelectric conversion efficiency of 32.14% was shown in indoor low light conditions, which significantly improved the photovoltaic performance of inorganic perovskite photovoltaic devices and had good thermal stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119233741A_ABST
    Figure CN119233741A_ABST
Patent Text Reader

Abstract

The invention discloses an application of a thiophene derivative in an inorganic perovskite photovoltaic device, the thiophene derivative is used as an additive for preparing a perovskite light absorption layer of the inorganic perovskite photovoltaic device, and the thiophene derivative is N-methylbenzo [b] thiophene-3-acetoxyl methylamine (NMTC). The NMTC is used as an additive to be added into an inorganic perovskite precursor solution, so that perovskite crystallization can be effectively regulated and controlled, and an inorganic perovskite thin film with excellent crystallization quality is obtained. An inorganic perovskite photovoltaic device of an inverted structure is further constructed based on the optimized inorganic perovskite thin film, the optimized device shows excellent photovoltaic performance under the conditions of standard sunlight and weak light, has good thermal stability, can be applied to outdoor and indoor scenes, and has a wider application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite photovoltaic devices, and in particular to the application of a thiophene derivative in an inorganic perovskite photovoltaic device. Background Art

[0002] Compared with organic-inorganic hybrid perovskites (OIHPs), inorganic cesium lead halide perovskites (CsPbX 3 ) has better thermal stability, so it is expected that CsPbX 3 The photovoltaic device is more suitable for actual working conditions. In addition, due to the 3 Perovskite has a wide band gap, and its absorption spectrum is more compatible with the indoor weak light spectrum, so its weak light photovoltaic performance is better. However, due to the low solubility of inorganic perovskite precursors in organic solvents, the precursor film prepared by the solution method crystallizes too quickly under thermal annealing conditions, resulting in small grains, more defects and grain boundaries, resulting in poor photovoltaic performance of the inorganic perovskite film, especially under weak light conditions, the actual photoelectric conversion efficiency is much lower than the theoretical value. In order to solve the above problems, previous work has reported a variety of additives based on inorganic salts, organic small molecules and polymers, which can improve the crystallization quality of inorganic perovskite films and photovoltaic performance under standard sunlight conditions by optimizing the crystallization process of inorganic perovskites. Because the concentration of photogenerated carriers in the perovskite light-absorbing layer is extremely low under weak light conditions, it is more sensitive to its defect state density, so how to effectively improve the weak light performance of inorganic perovskite devices still faces challenges. Summary of the invention

[0003] In order to solve the above technical problems, the primary purpose of the present invention is to provide an application of a thiophene derivative in an inorganic perovskite photovoltaic device. The thiophene derivative is used as an additive to optimize the crystallization process of the inorganic perovskite film and passivate the perovskite defects, thereby improving the photovoltaic performance of the inorganic perovskite photovoltaic device.

[0004] A further object of the present invention is to provide an inorganic perovskite photovoltaic device and a method for preparing the same. An inorganic perovskite photovoltaic device with an inverted structure is constructed based on the above inorganic perovskite film. The optimized device shows excellent photovoltaic performance under both standard sunlight and weak light conditions.

[0005] The present invention is achieved through the following technical solutions:

[0006] The first aspect of the present invention provides a thiophene derivative, wherein the thiophene derivative is N-methylbenzo[b]thiophene-3-acetylmethylamine (NMTC), having a structural formula of

[0007] The second aspect of the present invention provides a method for preparing the thiophene derivative described in the first aspect, comprising the following steps: dissolving benzo[b]thiophene-3-acetic acid in a methanol solution having a methylamine concentration of 2 to 3 M, and reacting to obtain the thiophene derivative.

[0008] In a specific embodiment, benzo[b]thiophene-3-acetic acid is dissolved in methylamine white crystals and placed in a container, a methanol solution with a methylamine concentration of 2 to 3 M is added dropwise, and the obtained mixed solution is subjected to ultrasonic treatment until the white crystals completely disappear, and the product after the complete reaction is dried to obtain N-methylbenzo[b]thiophene-3-acetylmethylamine.

[0009] The third aspect of the present invention provides an application of the thiophene derivative described in the first aspect in an inorganic perovskite photovoltaic device, especially an inverted inorganic perovskite photovoltaic device, wherein the thiophene derivative is used as an additive to prepare a perovskite light-absorbing layer of the inorganic perovskite photovoltaic device.

[0010] Thiophene derivatives can be used as additives to effectively regulate and optimize the crystallization of inorganic perovskite thin films to obtain a perovskite light-absorbing layer. The inverted photovoltaic device based on the perovskite light-absorbing layer has a photoelectric conversion efficiency of 16.08% under standard sunlight and shows excellent thermal stability. Under indoor weak light conditions (white light LED / 1000lx), the device also exhibits excellent photovoltaic performance and achieves a photoelectric conversion efficiency of 32.14%.

[0011] Furthermore, the perovskite light-absorbing layer is prepared by doping the thiophene derivative in a perovskite precursor solution.

[0012] Furthermore, the doping concentration of the thiophene derivative in the perovskite precursor solution is 0.1 to 1 mg / mL, preferably 0.5 to 1 mg / mL.

[0013] Furthermore, the perovskite precursor solution is CsPbI 2 Br precursor solution.

[0014] A fourth aspect of the present invention provides an inverted inorganic perovskite photovoltaic device, comprising a back electrode, a hole transport layer, a perovskite light absorption layer, an electron transport layer and a metal electrode arranged in sequence on one side of the back electrode, wherein the perovskite light absorption layer comprises a thiophene derivative, and the structural formula of the thiophene derivative is

[0015]

[0016] Furthermore, the back electrode is an ITO conductive substrate.

[0017] Furthermore, the hole transport layer is a mixed layer of Spiro-OMeTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene) and PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]).

[0018] Furthermore, the mass ratio of Spiro-OMeTAD to PTAA is (4-5):1.

[0019] Furthermore, the electron transport layer is ZnO / C 60 Layer or PC 61 BM(phenyl C 61 Methyl butyrate) layer.

[0020] Furthermore, it also includes a buffer layer arranged on the side of the electron transport layer away from the perovskite light absorbing layer. 61 In the case of BM, the buffer layer is BPhen (4,7-diphenyl-1,10-phenanthroline).

[0021] The fifth aspect of the present invention provides a method for preparing the inverted inorganic perovskite photovoltaic device according to the fourth aspect, comprising the following steps:

[0022] S1. Preparing a hole transport layer on the back electrode;

[0023] S2. Preparing a perovskite light absorbing layer on the hole transport layer described in S1;

[0024] S3. Preparing an electron transport layer on the perovskite light absorbing layer described in S2;

[0025] S4. Preparing a metal electrode on the electron transport layer described in S3 to obtain the inverted structure inorganic perovskite photovoltaic device;

[0026] or

[0027] S1. Preparing a hole transport layer on the back electrode;

[0028] S2. Preparing a perovskite light absorbing layer on the hole transport layer described in S1;

[0029] S3. Preparing an electron transport layer on the perovskite light absorbing layer described in S2;

[0030] S4. Preparing a buffer layer on the electron transport layer described in S3;

[0031] S5. Prepare a metal electrode on the buffer layer described in S4 to obtain the inverted structure inorganic perovskite photovoltaic device.

[0032] Furthermore, in S1, a step of pre-processing the back electrode is also included.

[0033] In a specific implementation manner, the back electrode is cleaned, dried, and then subjected to ultraviolet treatment.

[0034] Further, in S1 , a hole transport layer solution is spin-coated on the back electrode.

[0035] Furthermore, the hole transport layer solution may be a mixed solution of Spiro-OMeTAD and PTAA.

[0036] Furthermore, in the mixed solution of Spiro-OMeTAD and PTAA, the concentration of Spiro-OMeTAD is 4-5 mg / mL, and the concentration of PTAA is 1-2 mg / mL.

[0037] Furthermore, the spin coating speed is 7000-8000 rpm, and the spin coating time is 40-50 s.

[0038] Furthermore, in S2, the preparation of the perovskite light absorbing layer comprises the following steps: doping a thiophene derivative into a perovskite precursor solution, and coating the doped perovskite precursor solution on the hole transport layer.

[0039] Furthermore, in S2, the doped perovskite precursor solution is spin-coated on the hole transport layer, and the perovskite light absorbing layer is obtained after annealing.

[0040] Furthermore, the spin coating speed is 4000-5000 rpm, and the spin coating time is 30-40 s.

[0041] Furthermore, the annealing treatment conditions are: first annealing at 40-50° C. until the inorganic perovskite film appears light yellow, and then annealing at 130-140° C. for 5-10 minutes.

[0042] Furthermore, in S2, the thiophene derivative is prepared by the following method: dissolving benzo[b]thiophene-3-acetic acid in a methanol solution having a methylamine concentration of 2 to 3 M, and reacting to obtain the thiophene derivative.

[0043] Further, in S3, the electron transport layer solution is spin-coated on the perovskite light absorbing layer.

[0044] Furthermore, the electron transport layer solution can be an ethanol dispersion of 2-3 wt% ZnO nanoparticles and 20-30 mg / mL C 60 o-dichlorobenzene solution.

[0045] Further, the ethanol dispersion of ZnO nanoparticles is firstly spin-coated at a speed of 4000-5000 rpm for 30-40 seconds, and then the C60 The rotation speed of the o-dichlorobenzene solution is 2000-3000 rpm, and the spin coating time is 30-40 s.

[0046] Furthermore, when the electron transport layer is PC 61 When BM is used, the electron transport layer solution can be 20-30 mg / mL PC 61 The buffer layer solution may be a chlorobenzene solution of BM, and the buffer layer solution may be an ethanol solution of 0.5-1 mg / mL Bphen.

[0047] Further, in S3, PC is spin-coated 61 The rotation speed of the chlorobenzene solution of BM is 2000-3000 rpm, and the spin coating time is 30-40 s.

[0048] Further, in S4 , a buffer layer solution is spin-coated on the electron transport layer.

[0049] Furthermore, the spin coating speed is 4000-5000 rpm, and the spin coating time is 30-40 s.

[0050] Furthermore, a metal electrode is evaporated on the electron transport layer or the buffer layer.

[0051] Furthermore, the vacuum degree of the evaporation is 10 -4 ~10 -3 Pa.

[0052] Furthermore, the thickness of the hole transport layer is 10 to 20 nm, the thickness of the perovskite light absorption layer is 400 to 500 nm, the thickness of the electron transport layer is 40 to 50 nm, the thickness of the buffer layer is 1 to 2 nm, and the thickness of the metal electrode is 80 to 110 nm.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] The present invention provides a thiophene derivative N-methylbenzo[b]thiophene-3-acetylmethylamine (NMTC) and a preparation method and application thereof. The preparation method is simple and easy and suitable for mass preparation. Adding NMTC as an additive to an inorganic perovskite precursor solution can effectively regulate the crystallization of perovskite to obtain an inorganic perovskite film with excellent crystallization quality. Based on the optimized inorganic perovskite film, an inverted inorganic perovskite photovoltaic device is further constructed. The optimized device shows excellent photovoltaic performance and good thermal stability under both standard sunlight and weak light conditions, and can be applied to outdoor and indoor scenes, with a wider application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 is the nuclear magnetic resonance spectrum of NMTC prepared by the present invention; wherein a is1 H NMR diagram, b is 13 C NMR spectrum.

[0056] Figure 2 NMTC:CsPbI of Example 1 2 Schematic diagram of the structure of Br inorganic perovskite photovoltaic device.

[0057] Figure 3 NMTC:CsPbI in Example 2 2 Br film and CsPbI in Comparative Example 1 2 SEM images of Br films; wherein a is comparative example 1, and b is example 2.

[0058] Figure 4 NMTC:CsPbI in Example 2 2 Br film and CsPbI in Comparative Example 1 2 XRD patterns of Br thin films.

[0059] Figure 5 It is a current-voltage curve diagram of the inorganic perovskite photovoltaic devices of Examples 1 to 3 and Comparative Example 1 under standard sunlight.

[0060] Figure 6 The current-voltage curves of the inorganic perovskite photovoltaic devices of Example 4 and Comparative Example 2 under indoor weak light conditions.

[0061] Figure 7 The inorganic perovskite photovoltaic device of Example 2 and Comparative Example 1 is 2 The normalized photoelectric conversion efficiency changes with the placement time under the condition of 80°C in the atmosphere.

[0062] Figure 8 Graph showing the current-voltage curves of the inorganic perovskite photovoltaic devices of Example 2 and Comparative Example 1 under dark conditions. DETAILED DESCRIPTION

[0063] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0064] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0065] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0066] In the following examples, N-methylbenzo[b]thiophene-3-acetylmethylamine (NMTC) was prepared by the following method: at room temperature, 0.5 mmol of benzo[b]thiophene-3-acetic acid white crystals were weighed and added to a 3 mL small test bottle, and then 1 mL of a 2 M methanol solution of methylamine was added dropwise, and the mixed solution was placed under ultrasonic conditions for 1 hour until the white crystals completely disappeared. Then, the product after the complete reaction was vacuum dried at 60° C. for 10 hours, and the obtained white crystals were N-methylbenzo[b]thiophene-3-acetylmethylamine (NMTC).

[0067] The synthetic route of NMTC is:

[0068]

[0069] use 1 H and 13 The structure of the prepared NMTC was characterized by C NMR spectroscopy. The characterization results are shown in Figure 1 As shown. H NMR spectrum ( 1 H NMR) showed that δ (ppm) = 7.84 (m, 2H) and 7.32 (m, 3H) 1 The H signal can be attributed to the five hydrogens on the benzene ring and the heterocyclic ring, and δ(ppm)=2.74 (t, 3H) can be attributed to the three hydrogens on the aminomethyl group. 13 C NMR) showed that δ(ppm)=179.47 can be attributed to carbonyl carbon, δ(ppm)=141.97, 141.08, 133.97, 125.38, 125.13, 124.36, 123.82, 123.56 can be attributed to benzene ring and heterocyclic carbon, and δ(ppm)=25.64 can be attributed to methyl carbon. The above NMR results can prove that NMTC was successfully prepared.

[0070] Example 1

[0071] A NMTC:CsPbI 2 Br inorganic perovskite photovoltaic device, comprising an ITO conductive substrate (ITO electrode), a Spiro-OMeTAD and PTAA mixed layer (hole transport layer) sequentially arranged on one side of the ITO conductive substrate, and NMTC:CsPbI 2 Br thin film (perovskite light absorbing layer), ZnO / C 60 layer (electron transport layer), Ag electrode, such as Figure 2 As shown, it is prepared by the following method:

[0072] S1. Prepare a 20nm mixed layer of Spiro-OMeTAD and PTAA on an ITO conductive substrate: soak the ITO conductive substrate in detergent, ultrapure water, acetone, ethanol, and isopropanol solution and ultrasonically treat it, then place the cleaned ITO conductive substrate in a blast oven to dry for use. The ITO conductive substrate to be dried is cooled to room temperature, and then treated with an ultraviolet ozone cleaner to obtain a pretreated ITO conductive substrate. Spiro-OMeTAD and PTAA are dissolved in a mixture of tetrahydrofuran and chlorobenzene (volume ratio 9:1) at a mass ratio of 4:1, and a mixed solution is obtained after mixing at room temperature. The mixed solution is spin-coated on the ITO conductive substrate at a speed of 8000rpm and 40s, and then placed at room temperature for 5min.

[0073] S2. Preparation of 400 nm NMTC:CsPbI on Spiro-OMeTAD and PTAA mixed layer 2 Br perovskite light absorbing layer: Weigh 1 mg of NMTC and dissolve it in 1 mL of DMSO. Heat and stir at 60°C until it is completely dissolved to obtain a 1 mg / mL NMTC DMSO solution. Take 0.1 mL of the prepared 1 mg / mL NMTC DMSO solution and add it to 0.9 mL of CsPbI 2 Br perovskite precursor solution, mixed to obtain NMTC:CsPbI 2 Br perovskite precursor solution, NMTC:CsPbI 2 The concentration of NMTC in the Br perovskite precursor solution was 0.1 mg / mL. The precursor solution was spin-coated on the Spiro-OMeTAD and PTAA mixed layer at 4000 rpm for 35 s in a nitrogen environment, first annealed at 45°C until the film turned light yellow, and then annealed at 135°C for 5 min.

[0074] S3. In NMTC:CsPbI 2 Preparation of 40nm ZnO / C on Br perovskite light absorbing layer 60 Layer: 2.5 wt% ZnO nanoparticles in ethanol were spin-coated on NMTC:CsPbI at 4000 rpm for 30 s. 2 Br perovskite light absorbing layer, and then vacuum treated for 10 min to remove the non-volatile solvent; 20 mg / mL C 60 The o-dichlorobenzene solution was spin-coated on the ZnO layer at a rotation speed of 2000 rpm for 40 s, and vacuum treated for 10 min to remove the non-volatile solvent.

[0075] S4. In high vacuum (10 -4 Pa) under ZnO / C 60A 100 nm thick Ag electrode was deposited on the layer to obtain the NMTC:CsPbI 2 Br inorganic perovskite photovoltaic devices.

[0076] Example 2

[0077] A NMTC:CsPbI 2 Br inorganic perovskite photovoltaic device, comprising an ITO conductive substrate, a Spiro-OMeTAD and PTAA mixed layer (hole transport layer), NMTC:CsPbI 2 Br thin film (perovskite light absorbing layer), ZnO / C 60 layer (electron transport layer), Ag electrode, the preparation method is basically the same as that in Example 1, the difference is that: in S2, NMTC:CsPbI 2 The concentration of NMTC in the Br perovskite precursor solution was 0.5 mg / mL.

[0078] Example 3

[0079] A NMTC:CsPbI 2 Br inorganic perovskite photovoltaic device, comprising an ITO conductive substrate, a Spiro-OMeTAD and PTAA mixed layer (hole transport layer), NMTC:CsPbI 2 Br thin film (perovskite light absorbing layer), ZnO / C 60 layer (electron transport layer), Ag electrode, the preparation method is basically the same as that in Example 1, the difference is that: in S2, NMTC:CsPbI 2 The concentration of NMTC in the Br perovskite precursor solution was 1 mg / mL.

[0080] Example 4

[0081] A NMTC:CsPbI 2 Br inorganic perovskite photovoltaic device, comprising an ITO conductive substrate, a Spiro-OMeTAD and PTAA mixed layer (hole transport layer), NMTC:CsPbI 2 Br film (perovskite light absorbing layer), PC 61 The BM layer (electron transport layer), Bphen (buffer layer), and Ag electrode are prepared by the following method:

[0082] S1. Prepare a 20nm mixed layer of Spiro-OMeTAD and PTAA on an ITO conductive substrate: soak the ITO conductive substrate in detergent, ultrapure water, acetone, ethanol, and isopropanol solution and ultrasonically treat it, then place the cleaned ITO conductive substrate in a blast oven to dry for use. The ITO conductive substrate to be dried is cooled to room temperature, and then treated with an ultraviolet ozone cleaner to obtain a pretreated ITO conductive substrate. Spiro-OMeTAD and PTAA are dissolved in a mixture of tetrahydrofuran and chlorobenzene (volume ratio 9:1) at a mass ratio of 4:1, and a mixed solution is obtained after mixing at room temperature. The mixed solution is spin-coated on the ITO conductive substrate at a speed of 8000rpm and 40s, and then placed at room temperature for 5min.

[0083] S2. Preparation of 400 nm NMTC:CsPbI on Spiro-OMeTAD and PTAA mixed layer 2 Br perovskite light absorbing layer: Weigh 1 mg of NMTC and dissolve it in 1 mL of DMSO. Heat and stir at 60°C until it is completely dissolved to obtain a 1 mg / mL NMTC DMSO solution. Take 0.1 mL of the prepared 1 mg / mL NMTC DMSO solution and add it to 0.9 mL of CsPbI 2 Br perovskite precursor solution, mixed to obtain NMTC:CsPbI 2 Br perovskite precursor solution, NMTC:CsPbI 2 The concentration of NMTC in the Br perovskite precursor solution was 0.1 mg / mL. The precursor solution was spin-coated on the Spiro-OMeTAD and PTAA mixed layer at 4000 rpm for 35 s in a nitrogen environment, first annealed at 45°C until the film turned light yellow, and then annealed at 135°C for 5 min.

[0084] S3. In NMTC:CsPbI 2 Preparation of 40nm PC on Br perovskite light absorbing layer 61 BM layer: 20 mg / mL PC 61 The chlorobenzene solution of BM was spin-coated on NMTC:CsPbI at a speed of 2000 rpm for 40 s. 2 The Br perovskite light-absorbing layer was then vacuum treated for 10 min to remove the non-volatile solvent.

[0085] S4. On PC 61 Prepare a 2 nm Bphen layer on the BM layer: Spin coat a 0.5 mg / mL Bphen ethanol solution on the PC at 4000 rpm for 30 s. 61 The BM layer was vacuum treated for 10 min to remove the unvolatile solvent.

[0086] S5. In high vacuum (10 -4 Pa), an Ag electrode with a thickness of 100 nm was evaporated on the Bphen layer to obtain the NMTC:CsPbI 2 Br inorganic perovskite photovoltaic devices.

[0087] Comparative Example 1

[0088] A CsPbI 2 Br inorganic perovskite photovoltaic device, comprising an ITO conductive substrate, a Spiro-OMeTAD and PTAA mixed layer, a CsPbI 2 Br thin film (perovskite light absorbing layer), ZnO / C 60 layer (electron transport layer), Ag electrode, the preparation method is basically the same as that in Example 1, except that: in S2, CsPbI 2 The DMSO solution of NMTC was not added to the Br perovskite precursor solution.

[0089] Comparative Example 2

[0090] A CsPbI 2 Br inorganic perovskite photovoltaic device, comprising an ITO conductive substrate, a Spiro-OMeTAD and PTAA mixed layer, a CsPbI 2 Br film (perovskite light absorbing layer), PC 61 The preparation method of BM layer (electron transport layer), Bphen layer (buffer layer) and Ag electrode is basically the same as that of Example 4, except that: in S2, CsPbI 2 The DMSO solution of NMTC was not added to the Br perovskite precursor solution.

[0091] To explore the regulatory effect of NMTC as an additive on the inorganic perovskite film, the morphology and crystal structure of the perovskite light absorbing layer of Example 2 and Comparative Example 1 were characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. The characterization results are as follows: Figure 3 and Figure 4 As shown. Figure 3 It can be seen that with CsPbI 2 Compared with Br film, NMTC:CsPbI 2 The grain size of the Br film is larger and the grain boundary is smoother. Figure 4 It can be seen that with CsPbI 2 Compared with Br film, NMTC:CsPbI 2The diffraction peak of the Br film is stronger, indicating that the crystal quality of the film is better. The above SEM and XRD characterization results show that the NMTC additive can optimize the crystallization process of the perovskite film, and can simultaneously achieve the effects of passivation defects and regulation of crystallization, thereby obtaining a large-area uniform perovskite film with larger perovskite grains and better crystal quality.

[0092] Under standard sunlight conditions of AM 1.5G (Air Mass 1.5Global) (irradiation power of 100mW / cm 2 ) The photovoltaic performance of the inorganic perovskite photovoltaic devices of Examples 1 to 3 and Comparative Example 1 were tested respectively. The test results are as follows Figure 5 As shown in Table 1:

[0093] Table 1 Photovoltaic performance parameters of inorganic perovskite devices under standard sunlight

[0094] Test sample Open circuit voltage(V) <![CDATA[Short-circuit current (mA / cm 2 )]]> Fill factor (%) efficiency(%) Comparative Example 1 1.178 15.70 76.22 14.10 Example 1 1.198 16.32 78.74 15.40 Example 2 1.217 16.36 80.74 16.08 Example 3 1.228 16.05 78.72 15.53

[0095] from Figure 5 As can be seen from Table 1, the inorganic perovskite photovoltaic device of Example 2 has the best photovoltaic performance, and its open circuit voltage (V OC ) is 1.217V, short-circuit current (J SC ) is 16.36 mA·cm -2 , the filling factor (FF) is 80.74%, and the photoelectric conversion efficiency (η) is 16.08%, both of which are higher than the inorganic perovskite photovoltaic devices in Comparative Example 1 and other embodiments.

[0096] Under indoor weak light conditions (white light LED / 1000lx / irradiation power of 380μW / cm 2 ) The photovoltaic performance of the inorganic perovskite photovoltaic devices of Example 4 and Comparative Example 2 were tested respectively. The test results are as follows Figure 6 As shown in Table 2:

[0097] Table 2 Photovoltaic performance parameters of inorganic perovskite devices under standard sunlight

[0098] Test sample Open circuit voltage(V) <![CDATA[Short-circuit current (mA / cm 2 )]]> Fill factor (%) efficiency(%) Comparative Example 2 0.961 0.134 74.63 25.29 Example 4 1.042 0.145 80.70 32.14

[0099] from Figure 6 As can be seen from Table 2, the photoelectric conversion efficiency of the inorganic perovskite photovoltaic device of Comparative Example 2 is only 25.3%, and the efficiency of the inorganic perovskite photovoltaic device of Example 4 is 32.14%. This result shows that under weak light conditions, the photovoltaic performance of the inorganic perovskite photovoltaic device of Example 4 is significantly better than that of the inorganic perovskite photovoltaic device of Comparative Example 2.

[0100] The thermal stability of the inorganic perovskite photovoltaic devices of Example 2 and Comparative Example 1 was tested by 2When placed under 80℃ in the atmosphere, the normalized photoelectric conversion efficiency changes with the placement time as shown in the following figure. Figure 7 As shown in the figure, after 550 hours, the photoelectric conversion efficiency of the inorganic perovskite photovoltaic device of Comparative Example 1 is 73% of the initial efficiency, while the inorganic perovskite photovoltaic device of Example 2 can maintain 95% of the initial efficiency under the same conditions. This shows that compared with the inorganic perovskite photovoltaic device of Comparative Example 1, the photoelectric conversion efficiency of the inorganic perovskite photovoltaic device based on NMTC:CsPbI in Example 2 is 73% of the initial efficiency. 2 Inorganic perovskite photovoltaic devices with Br thin films have better thermal stability.

[0101] The dark current-voltage (JV) curves of the inorganic perovskite photovoltaic devices of Example 2 and Comparative Example 1 are shown in FIG. Figure 8 The inflection point of the curve, that is, the voltage corresponding to the inflection point where the current suddenly increases sharply with the increase of voltage, is usually defined as the trap filling limit voltage (V TFL ), the smaller the voltage value, the lower the defect state density. TFL About 1.25V, significantly lower than the V of Comparative Example 1 TFL (1.95 V), indicating that NMTC:CsPbI 2 Br film has a lower defect state density.

[0102] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. Application of a thiophene derivative in an inorganic perovskite photovoltaic device, characterized in that: The thiophene derivative is used as an additive to prepare a perovskite light-absorbing layer of an inorganic perovskite photovoltaic device. The structural formula of the thiophene derivative is 2. The use according to claim 1, characterized in that: The perovskite light-absorbing layer is prepared by doping the thiophene derivative in a perovskite precursor solution.

3. The use according to claim 2, characterized in that: The doping concentration of the thiophene derivative in the perovskite precursor solution is 0.1-1 mg / mL.

4. The use according to claim 2, characterized in that: The perovskite precursor solution is a CsPbI2Br precursor solution.

5. An inorganic perovskite photovoltaic device with an inverted structure, comprising a back electrode, a hole transport layer, a perovskite light absorption layer, an electron transport layer and a metal electrode arranged in sequence on one side of the back electrode, characterized in that: The perovskite light-absorbing layer comprises a thiophene derivative, and the structural formula of the thiophene derivative is 6. The inverted structure inorganic perovskite photovoltaic device according to claim 5, characterized in that: The hole transport layer is a mixed layer of Spiro-OMeTAD and PTAA, and the electron transport layer is ZnO / C 60 Layer or PC 61 BM layer.

7. The inverted structure inorganic perovskite photovoltaic device according to claim 5, characterized in that: It also includes a buffer layer arranged on a side of the electron transport layer away from the perovskite light absorbing layer.

8. A method for preparing an inverted structure inorganic perovskite photovoltaic device according to any one of claims 5 to 7, characterized in that: The following steps are involved: S1. Preparing a hole transport layer on the back electrode; S2. Preparing a perovskite light absorbing layer on the hole transport layer described in S1; S3. Preparing an electron transport layer on the perovskite light absorbing layer described in S2; S4. Preparing a metal electrode on the electron transport layer described in S3 to obtain the inorganic perovskite photovoltaic device with the inverted structure; or S1. Preparing a hole transport layer on the back electrode; S2. Preparing a perovskite light absorbing layer on the hole transport layer described in S1; S3. Preparing an electron transport layer on the perovskite light absorbing layer described in S2; S4. Preparing a buffer layer on the electron transport layer described in S3; S5. Prepare a metal electrode on the buffer layer described in S4 to obtain the inverted structure inorganic perovskite photovoltaic device.

9. The preparation method according to claim 8, characterized in that: In S2, the preparation of the perovskite light absorbing layer comprises the following steps: doping a thiophene derivative into a perovskite precursor solution, and coating the doped perovskite precursor solution on the hole transport layer.

10. The preparation method according to claim 8, characterized in that: In S2, the thiophene derivative is prepared by the following method: dissolving benzo[b]thiophene-3-acetic acid in a methanol solution having a methylamine concentration of 2 to 3 M, and reacting to obtain the thiophene derivative.